EZZEePOT ease of use perception study - Mohd Hafiz Abdul Halim; Franklin Hazley Lai; Syahrul Nizam Salam (International Journal of Technical Vocational and Engineering Technology, 2024)
The main challenge that Kona Bites is dealing with is the lack of an application for recording financial transactions online. Therefore, the study leads to the implementation of the ADDIE model to plan the development of the EZZEePOT mobile application (Gustafson & Branch, 2001) and further analyze the commercialization potential through SWOT, TOWS and 4P analysis. The factors influencing the perceived ease of use of EZZEePOT are also analyzed in this study in accordance with the Venkatesh et al. (2003) Theory of Acceptance and Use of Technology (UTAUT). 12 staff members of Kona Bites who use the application every working day represent the study sample. Sampling using purposive sampling and data analysis using GNU software, PSPP. The data is interpreted based on percentage values, mean and standard deviation. The results of the study show that the commercialization potential of the EZZEePOT mobile application to Kona Bites staff can be extended to Small and Medium Industries (SME) businesses. The results of this study show that Kona Bites staff have a significantly high influence on the intention to actually use this application for the factors of performance expectancy and effort expectancy. Therefore, this factor has a significant effect on the actual use of the EZZEePOT application. Nevertheless, the results of this study show that Kona Bites staff have a moderately significant influence on the intention to actually use this application for the facilitating conditions factor.